Itelligent food saver - Catalina Stanca (IUL Research)
This paper presents an example of good practice, a project developed by a group of high school students together with their science teachers. “Intelligent Food Saver” is an autonomous robot developed as a solution of one of the major problems related to food waste in households. Its multiple functions such as storage of perishable food, choose the aliments depending on the recipes selected, suggest recipes which can provide an optimum caloric content for a week or suggest recipes depending on the expiry date of the aliments lead us to believe that it can be an alternative for food waste. We consider that “Intelligent Food saver” is a result of a scientific research that combines computer – based education and hands-on-learning.